Estudo químico, farmacológico e aplicação de métodos computacionais na elucidação estrutural de constituintes químicos de folhas de Maytenus acanthophylla Reissek (Celastraceae) - Djalma Menezes de Oliveira (2012)
The aim of this work was to deal with the chemical and pharmacological studies Maytenus acanthophylla Reissek (Celastraceae) leaves, a medicinal plant of Bahia (holy thorn). The general objective was the systematic investigation of the plant`s chemical and pharmacological potential and the ability to provide renewable materials. The study material was collected from specimens found in the region of Chapada Diamantina in the state of Bahia. In this study we transcribed methods, philosophies of work and results obtained in the phytochemical study, as well as the results of biological tests made with some isolated compounds and extracts. The structures of these compounds were elucidated by spectroscopic techniques (NMR 1D and 2D, IES-EM, GC-EM, IV, UV and X-rays diffraction) with the support of database and computer programs for ab initio calculations and molecular modeling. The phytochemical study allowed the isolation of thirty chemical compounds, including 21 pure and nine constituting mixtures. Three new flavonoids were isolated in methanol and methanol/water extracts: 3-O-{[-L-rhamnopyranosyl(16)]-O-[-D-xylopyranosyl(13)-O--L-rhamnopyranosyl(12)]}--D-quercetin galactopyranoside (21), 3-O-{[-L-rhamnopyranosyl(16)]-O-[-D-xylopyrano-syl(13)-O--L-rhamnopyranosyl(12)]}--D-kaempferol galactopyranoside (22), 3-O-{[-L-rhamnopyranosyl(16)]-O-[-D-xylopyranosyl(13)-O--L-rhamnopyranosyl(12)]}--D-isorhamnetin galactopyranoside (23); and one triglucoside flavonoid previously isolated: 3-O-{[-L-rhamnopyranosyla(16)][-L-rhamnopyranosyla(12)]}--D-quercetin galactopyra-noside (20). In the hexane and ethyl acetate extracts, the isolated constituents consist of a mixture of hydrocarbons (1), squalene (2), 1,4-trans-polyisoprene (gutta-percha,3), a fatty alcohol (4); seven pentacyclic triterpenes (TTPC) friedelan: friedelin (5), 3friedelinol (6), 3-friedelinol (7), 28-hydroxy-3-oxo-friedelan (canophyllol, 13), 3,16- dihydroxy friedelan (pachysandiol B, 14), 3,24-dihydroxyfriedelan (15) and 3,24-diacetoxyfriedelan (15a). Compounds 14 and 15 were isolated for the first from the Celastraceae family. Two TTPC lupanes were also isolated: 3-lup-20(29)-en-3-ol (lupeol, 8) and 3-lup-20(29)-en-3-ila acetate (9); as well as the isomer mixture 3-estearyloxy-olean-12-eno (10) and 3-estearyloxy-urs-12-eno (11). TTPC 11 a - amyrin (12), - sitosterol (16) and eicosanoic acid (17) were also isolated pure in hexane or ethyl acetate extracts. By means of GC-MS seven monosaccharides (18) were detected and galactitol (19) was isolated pure in methanol/water extracts, which allowed to obtain the derivative 1,2,3,4,5,6-hexa-galactitol acetate (19a). The polymer 3 was used to formulate antibiotic and antiseptic products for use in dentistry, which generated a request for patent registration by UFMG. In biological tests, the methanol extract showed significant analgesic activity in mice; however, in microbial and cytotoxic tests the extracts of leaves showed no toxic or inhibitory action against tumor cells (MCF-7, TK10 and UACC-62), micro-organisms (bacteria and Candida species), or the protozoan leishmaniasis. However, in tests with solutions of 19a on chloroplasts from Spinacia oleracea L. we observed an inhibition of ATP synthesis which indicated that 19a can be a model for herbicides synthesis. In capture tests of DPPH free radicals in solution, glycosides 21 and 22 showed good activity and 23 showed immunomodulating effects in tests of proliferation of mononuclear cells from human blood. In light of the results, considering the diversity of the obtained compounds, it was possible to visualize the great chemical and pharmacological potential of Maytenus acanthophylla and to recognize, through scientific means, the validity of using its leaves in popular medicine.